Design of LDPC Coded Multi-User Massive MIMO Systems With MMSE-Based Iterative Joint Detection and Decoding - Han Jin Park; Jeong Woo Lee (IEEE Access, 2023)
We design a low-density parity-check (LDPC) coded multi-user massive multiple-input multiple-output (MIMO) system to achieve a high error correcting capability with a fast convergence speed of iterative joint detection and decoding (JDD) process employing a low-complexity detection. Minimum mean squared error detection with parallel interference cancellation (MMSE-PIC) and its variations are considered as low-complexity linear detection algorithms. We provide a factor graph representation of LDPC coded multi-user massive MIMO system using JDD algorithm employing MMSE-PIC detection, and we formulate updating rules of messages flowing in the JDD process. We propose a practical and efficient tool for analyzing the extrinsic information transfer (EXIT) characteristics of messages exchanged between detector and decoder, based on which LDPC codes and JDD strategy are jointly designed to result in a low bit error rate (BER) and a fast convergence speed of JDD mechanism. It is observed that the error correcting capability and JDD convergence behavior predicted by the proposed analysis tool match well the actual performances obtained by simulations. It is also observed that LDPC coded multi-user massive MIMO system employing LDPC codes and JDD strategy designed optimally by the proposed EXIT analysis tool achieves a lower BER with a faster convergence speed.